2020
DOI: 10.2196/23578
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Approach to Assessing Differentiation Degree and Lymph Node Metastasis of Extrahepatic Cholangiocarcinoma: Prediction Using a Radiomics-Based Particle Swarm Optimization and Support Vector Machine Model

Abstract: Background Radiomics can improve the accuracy of traditional image diagnosis to evaluate extrahepatic cholangiocarcinoma (ECC); however, this is limited by variations across radiologists, subjective evaluation, and restricted data. A radiomics-based particle swarm optimization and support vector machine (PSO-SVM) model may provide a more accurate auxiliary diagnosis for assessing differentiation degree (DD) and lymph node metastasis (LNM) of ECC. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…With the development of precision medicine and artificial intelligence, radiomics has appeared as a new medical field that is able to capture and quantify lesion heterogeneity, especially for lesions in oncology patients, by extracting and analyzing the quantitative texture features (39). Importantly, we have made great efforts and obtained some amazing results about radiomics analysis in recent years (40)(41)(42). In this study, we first extracted 396 radiomics features from each ALN in the CECT images, and used all of the radiomics features to develop the radiomics model for discriminating ALN status in patients with breast cancer based on the SVM algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of precision medicine and artificial intelligence, radiomics has appeared as a new medical field that is able to capture and quantify lesion heterogeneity, especially for lesions in oncology patients, by extracting and analyzing the quantitative texture features (39). Importantly, we have made great efforts and obtained some amazing results about radiomics analysis in recent years (40)(41)(42). In this study, we first extracted 396 radiomics features from each ALN in the CECT images, and used all of the radiomics features to develop the radiomics model for discriminating ALN status in patients with breast cancer based on the SVM algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Besides CT radiomic, Yao et al . studied patients with extrahepatic cholangiocarcinoma by extracting radiomic features from images obtained with precontrast T1‐weighted imaging, T2‐weighted imaging, and diffusion‐weighted imaging, and a radiomic model could predict lymph node metastasis of extrahepatic cholangiocarcinoma with an AUC of 0.89 44 . Those studies suggest that analysis of CT/MRI radiomic features may assist in predicting lymph node metastasis in biliary cancers.…”
Section: Biliary Diseasesmentioning
confidence: 91%
“…The literature search and study selection was shown in Figure 1. The included studies were published between 2018 and 2021 (four contract-CT based on radiomics studies (18,28,29) and three MRI based on radiomics studies (19,(30)(31)(32) were included in the meta-analysis). A total of 977 BTCs patients were included.…”
Section: Literature Searchmentioning
confidence: 99%